Pengaruh Model Discovery Learning Terhadap Hasil Belajar Siswa Pada Tema 5 Subtema 1 Kelas V Di UPTD SDN Tunjung 2 - Putri, Dela Lorensya; Fajrin, Nilamsari Damayanti (Yayasan Arrahman Nahdlatul Wathan, 2024)
This research aims to determine whether there is a significant influence of the discovery learning model on student learning outcomes in Theme 5 Subtheme 1 at UPTD SDN Tunjung 2. This research is a quantitative type of experimental research, the design used is a pre-experimental design in the form of a one group pretest posttest design. Data was collected using observation and tests. The results of this research show that the discovery learning model has an influence on student learning outcomes.. Based on hypothesis test calculations using the paired sample t-test, the tcount is 10.337 and the ttable is 2.060, the significance value is 0.000. Based on the test criteria, if tcount > ttable then Ha is accepted and H0 is rejected. It can be stated that the value of tcount > ttable is 10.337 > 2.060 so that Ha is accepted and H0 is rejected, whereas if the result is Sig.2 (tailed) < 0.05 or 0.000 < 0.05 then H0 is rejected and Ha is accepted. Based on this, it can be concluded that there is a significant influence of the application of the discovery learning model on student learning outcomes in Theme 5 Sub-theme 1 at UPTD SDN Tunjung 2.